Advances in the application of robotic surgical systems to gastric cancer: A narrative review - Shixun Ma; Li Li; Chongya Yang; Bin Liu; Xiang Zhang; Tianyi Liao; Shuo Liu; Haojie Jin; Hui Cai; Tiankang Guo (Asian Journal of Surgery, 2023)
Gastric cancer is one of the common malignant tumors in the gastrointestinal tract, and surgery is currently an important treatment for progressive gastric cancer. With the development of technology, the simultaneous maturation of artificial intelligence (AI), fifth-generation (5G) telecommunication networks and the internet of things (IOT) has brought significant efficacy and new opportunities for the surgical treatment of gastric malignancies. The combination of 5G network and remote surgical robotic system is the future trend of radical gastric cancer surgery, and the “unmanned” treatment mode of fully automated robotic gastric cancer radical surgery will be realized soon.